Role of deep medullary veins in pathogenesis of lacunes: Longitudinal observations from the CIRCLE study. Issue 9 (September 2020) - Zhou, Ying; Li, Qingqing; Zhang, Ruiting; Zhang, Wenhua; Yan, Shenqiang; Xu, Jinjin; Wang, Shuyue; Zhang, Minming; Lou, Min
Our purpose is to assess the role of deep medullary veins in pathogenesis of lacunes in patients with cerebral small vessel disease (cSVD). We included patients with baseline and 2.5-year follow-up MRI in CIRCLE study. Susceptibility Weighted Imaging-Phase images were used to evaluate deep medullary veins based on a brain region-based visual score, and T2-Fluid-Attenuated-Inversion-Recovery images were used to evaluate lacunes. Cerebral blood flow and microstructural parameters in white matter hyperintensities and normal appearing white matter were also analyzed. A total of 203 cSVD patients were analyzed and 101 (49.8%) patients had baseline lacunes. Among them, 64 patients had follow-up MRI, including 16 (25.0%) with new lacunes. The patients' deep medullary veins median score was 9 (7–12). At baseline, high deep medullary veins score was independently associated with the presence of lacunes after adjusting for age, diabetes mellitus, white matter hyperintensities volume and cerebral blood flow or white matter microstructural parameters (all p  <   0.001). Longitudinally, high deep medullary veins score was independently associated with new lacunes after adjusting for gender ( p  <   0.001). The association was also independent of white matter hyperintensities volumes, cerebral blood flow or white matter microstructural parameters (all p  <   0.05). Our results suggest that deep medullary veins disruption might be involved in pathogenesis of lacunes.